Image-guided optimization of current steering in STN-DBS for Parkinson's disease - Umemura, Atsushi; Mizuno, Hideki; Maki, Mina; Masago, Atsuo (Frontiers in Neurology, 2025)
ObjectiveRecent advancements in multiple independent current control (MICC) technology, combined with directional leads, have improved clinical outcomes in subthalamic nucleus deep brain stimulation (STN-DBS) for Parkinson's disease (PD). However, these advancements have also increased the complexity and duration of programming. This study aimed to evaluate the clinical utility of image-guided programming (IGP) in patients with stable postoperative symptoms.MethodsSixteen patients with advanced PD, who had undergone STN-DBS and exhibited stable symptoms for at least 6 months under conventional programming, were enrolled. An alternative stimulation program was developed using Stimview™ XT, a patient-specific image-guided interface, without altering pulse width or frequency. Stimulation fields were modified using horizontal and vertical current steering based on individual STN anatomy. Motor function was evaluated via the Unified Parkinson's Disease Rating Scale part III (UPDRS III) before, 1 h after, and 3 months post-reprogramming.ResultsImage-guided current steering resulted in modifications in 29 of the 32 leads. Horizontal steering was newly introduced in 23 leads, while vertical adjustments were made in six leads. Nine patients reported immediate subjective improvement, and 15 of 16 opted to continue with the IGP-derived settings. Statistically significant improvements in Unified Parkinson's Disease Rating Scale (UPDRS) part III scores were observed 1 h after reprogramming (P < 0.05), and these improvements were sustained at the 3-month follow-up.ConclusionsIGP provides a clinically effective, time-efficient strategy for refining current steering in STN-DBS, even in patients with stable symptoms under conventional settings. By leveraging individualized anatomical visualization, IGP enhances precision in targeting the dorsolateral STN, resulting in improved motor outcomes.